Virtual Laboratory in Physics Education: Penguasaan Konsep Mahasiswa dalam Mata Kuliah Fisika Inti - Firdaus, Thoha; Sinensis, Arini Rosa; Effendi (Universitas Nurul Huda, 2023)
Virtual Laboratory (V-Lab) is a media platform for interaction and visualization of learning for practicum-based courses. V-Lab is a solution to learning problems due to the lack of real laboratory facilities as well as an alternative for practicums that require a high level of safety. The purpose of this study was to determine students' mastery of concepts after using the V-Lab in the core Physics course. The method used is quasi-experimental. The research subjects were 15 Unuha physics education students. The data collection technique is a concept mastery test. The results showed that the increase in mastery of the concept was 0.432 with moderate criteria, while based on the paired sample test, it was known that the sig. (2-tailed) is 0.000 <0.05, then Ho is rejected and Ha is accepted. So it can be concluded that there is an average difference between pre-test and post-test concept mastery, which means that there is an influence of V-Lab application in increasing mastery of core physics concepts. The data shows that the Virtual Laboratory is effectively used to improve mastery of the concepts of core physics courses.